2019
DOI: 10.20473/jvhs.v2.i2.2018.86-91
|View full text |Cite
|
Sign up to set email alerts
|

Therapy for Irregular Menstruation With Acupunture and Herbal Pegagan (Centella Asiatica (L.))

Abstract: Background : Menstruation is bleeding periodic scale and cyclical from uterus extrication (deskuamasi) endometrium. Menstruation bleeding is complex interaction result wich involve hormone system and body system, that are hypothalamus, hypofisis, ovarium and uterus. Every woman has different menstruation cycle. The causes of irregular menstruation are genetic and bad habit life. While according to TCM, irregular menstruation is Yue Jing Bu Tiao. Purpose : to knowing the effect of acupuncture therapy and point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
6
0
9
Order By: Relevance
“…In previous research, the snake and ladder game was known as an effective learning strategy for conveying and applying a lot of information (Suratno, 2020). This was because in this game there had been many messages in the form of writing, letters, pictures, and symbols that encouraged participants to involve more than one of their five senses to interpret them (Nachiappan, 2017;Prayuni et al, 2018). In other study, the simulation method with the game of snakes and ladders had been shown to be able to make a passive learning atmosphere become active which allowed them to capture more information effectively and efficiently though the had been discussing difficult things (Annamalai et al, 2015;Martín-García et al, 2020;Nachiappan, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research, the snake and ladder game was known as an effective learning strategy for conveying and applying a lot of information (Suratno, 2020). This was because in this game there had been many messages in the form of writing, letters, pictures, and symbols that encouraged participants to involve more than one of their five senses to interpret them (Nachiappan, 2017;Prayuni et al, 2018). In other study, the simulation method with the game of snakes and ladders had been shown to be able to make a passive learning atmosphere become active which allowed them to capture more information effectively and efficiently though the had been discussing difficult things (Annamalai et al, 2015;Martín-García et al, 2020;Nachiappan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of knowledge, nature, and risky behavior for adolescents that have an impact on reproductive health status requires the availability of health services that meet the health needs of adolescents, especially services for reproductive health that are friendly to adolescents (Prayuni et al, 2018). Currently, several methods of health education regarding adolescent reproductive health have been developed, including lectures and discussions, focus group discussions, games and peer groups (Ambrose, 17 C.E.…”
mentioning
confidence: 99%
“…Dysminorea merupakan nyeri yang dirasakan saat menstruasi. Nyeri ini disebabkan oleh adanya hormone prostaglandin yang membuat otot uterus berkontraksi (Prayuni, 2019).…”
Section: Knowledge Perception and Behavior With A P-value <0001 Concl...unclassified
“…Siklus menstruasi adalah waktu sejak hari pertama menstruasi sampai datangnya menstruasi periode berikutnya. Siklus menstruasi pada wanita normalnya berkisar 21-35 hari, lama menstruasi 3-5 hari (Prayuni, Imandiri and Adianti, 2019). Ketika menstruasi sering disertai beberapa keluhan yaitu dismenore.…”
Section: Pendahuluanunclassified